2016
DOI: 10.1016/j.landusepol.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high crop prices on the use of agro-chemical inputs in France: A structural econometric analysis

Abstract: World crop prices increased dramatically during the period 2006-2009. In this context of high crop prices, farmers may tend to increase the amount of agro-chemical inputs they use in order to increase yield and manage risks related to crop production. These practices could, however, have potentially adverse environmental effects in terms of loss of biodiversity and increased water and air pollution. This study uses a structural econometric model to measure the effects of crop prices on demand for agro-chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
4
7
0
Order By: Relevance
“…Such studies take into account cross-price elasticities between different products and estimate crop acreage responses to price changes; they deal with the estimation of models to measure how prices affect farmers' production decisions (e.g. Bayramoglu and Chakir, 2016;Haile et al, 2016;Kim and Moschini, 2018). However, it is worth of mention the difficulty of comparing estimates from studies that differ in scope, data, and estimation methods.…”
Section: Evidence From Previous Studiesmentioning
confidence: 99%
“…Such studies take into account cross-price elasticities between different products and estimate crop acreage responses to price changes; they deal with the estimation of models to measure how prices affect farmers' production decisions (e.g. Bayramoglu and Chakir, 2016;Haile et al, 2016;Kim and Moschini, 2018). However, it is worth of mention the difficulty of comparing estimates from studies that differ in scope, data, and estimation methods.…”
Section: Evidence From Previous Studiesmentioning
confidence: 99%
“…Several interacting factors determine which pesticides, and how much, are used in crop production: cropping system, national legislation, pressure from weeds, pests and diseases, climate, weather, year (some pests are cyclical), and commodity prices. For example, Bayramoglu and Chakir (2016) showed that higher prices correlate positively with a higher demand for agro-chemical inputs such as pesticides. Here, the roles of cropping system and legislation are discussed, focusing on the situations in Brazil and Sweden.…”
Section: Pesticide Usementioning
confidence: 99%
“…However, currently available MEMC models ignore or poorly describe an important decision of crop producers: their choice to produce a subset of crops among the set of crops they can produce and sell. Indeed, applications of MEMC models frequently ignore null acreages by relying either on very specific farm samples (e.g., Just et al, 1983Just et al, , 1990Bayramoglu and Chakir, 2016) or on crop aggregation that eliminate null crop acreages (e.g., Oude Lansing and Peerlings, 1996;Serra et al, 2005;Oude Lansink, 2008;Letort, 2012, 2014). 1 Yet, sample selection prevents extrapolation of the estimation results to farmers not producing all considered crops while crop aggregation induces information losses regarding production choices at the crop level.…”
Section: Introductionmentioning
confidence: 99%